Pengaruh tingkat pengetahuan, sikap dan perilaku dengan kejadian COVID-19 pada mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan Universitas Warwadewa - Agus Santosa; Luh Gde Evayanti; Angga Priyana (Intisari Sains Medis, 2022)
Introduction: Efforts in preventing COVID-19 are carried out by increasing knowledge and improving attitudes and behavior. These three components affect the occurrence of COVID-19, especially among medical students. This study aimed to determine the relationship between knowledge, attitudes, and behavior and the incidence of COVID-19 in students of the Faculty of Medicine and Health Sciences (FKIK Unwar). Methods: Analytical design and a cross sectional study were used. The study was conducted from October – November 2021. Several 88 samples were selected by purposive sampling from 2018-2020 class students in the Unwar FKIK environment. Data were analyzed using Fisher Exact test (p<0.05). Results: Medical students have knowledge of 94.3% in the good category, 79.5% positive attitude and 55.7% positive behavior towards COVID-19, although there is no significant relationship (p>0.05). Conclusion: Education and implementation of strict health protocols at FKIK Unwar increase the knowledge, behavior, and attitudes of FKIK Unwar students. Those were related to the low incidence of COVID-19 at FKIK Unwar for the last 3 months.   Latar Belakang: Peningkatan pengetahuan, perbaikan sikap serta perilaku dilaksanakan dalam upaya pencegahan COVID-19. Ketiga komponen tersebut mempengaruhi kejadian COVID-19 terutama dikalangan mahasiswa kedokteran. Penelitian ini bertujuan mengetahui pengaruh tingkat pengetahuan, sikap dan perilaku dengan kejadian COVID-19 pada mahasiswa Fakultas Kedokteran dan Ilmu Kesehatan (FKIK Unwar). Metode: Rancangan analitik ini menggunakan studi cross sectional dan dilaksanakan pada bulan Oktober – November 2021. Sebanyak 88 sampel dipilih dengan purposive sampling dari mahasiswa angkatan 2018-2020 di lingkungan FKIK Unwar. Data dianalisis sengan uji Fisher Exact (p<0,05). Hasil: Mahasiswa kedokteran memiliki pengetahuan persentase 94,3% dalam kategori baik, sikap positif 79,5% dan perilaku positif 55,7% terhadap COVID-19 meskipun tidak terdapat pengaruh bermakna (p>0,05). Simpulan: Edukasi dan penerapan protokol kesehatan yang ketat di FKIK Unwar meningkatkan pengetahuan, perilaku, dan sikap mahasiswa FKIK Unwar. Hal ini terkait rendahnya kejadian COVID-19 di FKIK Unwar selama 3 bulan terakhir.